Instructional Strategies and Its Relationship with Learning Orientation and Mental Focus for Students of Tishreen University A Field Study - Jnad, Rawa (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The purpose of this study was to determine the level of Learning Orientation and Mental Focus for students of Tishreen University. This study also aimed at investigating affection of many variables on students` Learning Orientation and Mental Focussuch as instructional strategies, gender and specialization. Sample consisted of (672) students from Tishreen University in academic year (2016-2017). The Results Of This Study Showed:  The most preferred strategies by students are interactive Strategies; (57.4%) of students prefer to learn by using of interactive strategies.  Students of Tishreen University have a very good level of Learning Orientation (77.46%) and Acceptable level of Mental Focus (57.98%).  There is no a statistical difference between students` mean scores on scale of Learning Orientation contributed to gender variable, but There is a statistical difference between students` mean scores on scale of Mental Focus contributed to gender variable. This difference is in favor of males.  Learning Orientation are affected by Instructional Strategies; the students who prefer interactive strategies have mental focus more than students who prefer show strategies. The study recommended to continue in investigating for variables that increase with Learning Orientation and Mental Focus.